Proceedings of the 56th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2018
DOI: 10.18653/v1/p18-1077
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Relational Question Answering from Narratives: Machine Reading and Reasoning in Simulated Worlds

Abstract: Question Answering (QA), as a research field, has primarily focused on either knowledge bases (KBs) or free text as a source of knowledge. These two sources have historically shaped the kinds of questions that are asked over these sources, and the methods developed to answer them. In this work, we look towards a practical use-case of QA over user-instructed knowledge that uniquely combines elements of both structured QA over knowledge bases, and unstructured QA over narrative, introducing the task of multirela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…We use the Document Reader (DrQA) model of Chen et al (2017), which has demonstrated strong performance on multiple datasets (Rajpurkar et al, 2016;Labutov et al, 2018). Because DrQA requires text spans as answers during training, we select the span that has the highest lexical overlap (F1 score) with the original answer as the gold answer.…”
Section: Reading Comprehension Modelsmentioning
confidence: 99%
“…We use the Document Reader (DrQA) model of Chen et al (2017), which has demonstrated strong performance on multiple datasets (Rajpurkar et al, 2016;Labutov et al, 2018). Because DrQA requires text spans as answers during training, we select the span that has the highest lexical overlap (F1 score) with the original answer as the gold answer.…”
Section: Reading Comprehension Modelsmentioning
confidence: 99%
“…• DrQA: Chen et al (2017) introduced a simple but effective neural network-based model for the MRC task. DrQA Reader achieved good performance on multiple MRC datasets (Rajpurkar et al, 2016;Reddy et al, 2019;Labutov et al, 2018). Thus, we re-implement this method into our dataset as the first baseline models to compare future models.…”
Section: Re-implemented Methods and Baselinesmentioning
confidence: 99%
“…For the machine reading comprehension model, the Document Reader (DrQA) introduced by Chen et al [1] is a powerful model on various of machine reading comprehension corpora such as: SQuAD [11], TextWorldsQA [8], and UIT-ViSQuAD [10]. The DrQA model consists of two modules: Document Retriever and Document Reader.…”
Section: Methodologiesmentioning
confidence: 99%